Phylogenetic Relationships of Species of Hypselobarbus (Cypriniformes: Cyprinidae): An Enigmatic Clade Endemic to Aquatic Systems of India - Arunachalam, M.; Raja, M.; Muralidharan, M.; Mayden, Richard L. (Zootaxa, 2012)
Very little is known about the diversity and systematics of the genus cypriniform genus Hypselobarbus. Currently, the genusincludes at least eleven species, all endemic to freshwater systems of Peninsular India. While these species are commonlyknown in India and are frequently used as a food source, little is known about the morphological diversity within and betweenspecies and nothing is known regarding intraspecific genetic diversity or species relationships. Herein, we examine the geneticdiversity in the genus for 11 mitochondrial genes for eleven populations representing nine of the known 11 species.Hypselobarbus is resolved as monophyletic, with the inclusion of P. carnaticus, and species relatioships are very stronglysupported. Because of the unambiguous relationships strongly supported B. carnaticus is allocated to Hypselobarbus. Thisresearch and ongoing morphological and molecular work with the genus supports the existence of additional new species inpeninsular India in need of further molecular and morphological study. Genetic diversity in the genus is high; for the twospecies wherein more than one sample, and the two of each are suspected to represent undescribed taxa, these populationsexhibited greater genetic divergence than that observed between any two of the other currently recognized species,corroborating our hypothesis based on morphological evidence. Clearly the genus warrants more thorough geographicsampling and examination of morphological and molecular data/analyses to reveal the natural lineages existing in this endemic and enigmatic genus.